Baker's cyst: types of its course, sonographic guidance, and treatment - N A Khitrov (Современная ревматология)
Baker's cyst (BC), a fluid-expanded synovial sac in the popliteal space, frequently occurs in arthrosis, arthritis, and traumatic knee joint injury. The outcomes of BC may be suppuration, rupture, or a chronic pattern. Knowledge of the causes of this abnormality, its clinical picture and the specific features of its ultrasound diagnosis assists in elaborating the treatment policy of this disease.